DEVELOPING CULTURE-BASED EFL MODULES: WEST JAVANESE FOLKLORE FOR ENHANCING STUDENT ENGAGEMENT IN SENIOR HIGH SCHOOL - Syamsi Edi; Leroy Holman Siahaan; Iswandini Agustin; Cherry Alifya; Nur Aryaningsih; Jihan Auliatul Alifah (University of Kuningan, 2025)
The Education plays a crucial role in national development, yet Indonesia still faces challenges in English language proficiency, ranking 80th out of 116 countries according to EF. At the same time, globalization has influenced young learners to adopt foreign cultures, putting local heritage such as folklore at risk of being forgotten. This study aims to integrate English language learning with the preservation of local culture by developing English teaching materials for Senior High School students for X, XI, XII graders based on West Java folklore. The research employed a Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. In the Define stage, learning needs, student characteristics, and objectives were identified. The Design stage focused on structuring content, learning activities, and evaluation instruments. The Develop stage involved expert validation and limited trials of the teaching materials. Finally, in the Disseminate stage, the materials were prepared for wider distribution in both print and digital formats. The findings indicate that folklore-based teaching materials not only enhance students’ English skills—listening, speaking, reading, and writing—but also foster cultural awareness and appreciation. In addition, this study demonstrated that the development of English teaching materials based on West Javanese folklore significantly improved students' language skills and cultural awareness. The integration of local folklore not only enhanced language proficiency in listening, speaking, reading, and writing but also fostered a deeper connection to students' cultural heritage. It is recommended that educators incorporate folklore-based materials into English curricula to bridge the gap between language learning and cultural preservation. Future research should expand the use of such materials across different regions to further validate their effectiveness in diverse cultural contexts.